PW 1961 Homicide rates three times higher than suicide rates in adult men in the indian state of bihar. (November 2018) - Dandona, Rakhi; Kumar, G Anil; George, Sibin; Akbar, Md; Dandona, Lalit
Abstract : Little is known about intentional injury deaths in India. We report epidemiology of intentional injury deaths in adults from a population-based study in the Indian state of Bihar with a population of over 100 million. Interviews were conducted using the Population Health Metrics Research Consortium shortened verbal autopsy questionnaire for deaths in >15 years age group that occurred between January 2012 to March 2014 in 1 09 689 households in 1 017 clusters representative of the state with a participation rate 87.1%. Cause of death was assigned using the SmartVA automated algorithm. The annualized suicide and homicide mortality incidence by sex and place of residence were estimated. The survey covered 3 68 800 population aged >15 years and 6386 deaths from all causes were identified. The adjusted suicide rate was estimated at 4.9 (95% CI 4.6–5.1) and 3.6 (3.4–3.8) per 1 00 000 population for men and women, respectively. This rate was higher in the rural areas (6.5, 6.2–6.7) and was the highest in 25–34 years age group (7.4, 6.9–7.4). Personal reasons (63%) accounted for most suicides, and poisoning (48.9%) followed by hanging (32.5%) were the most common modes of suicide. The homicide rate estimated in men at 18.1 (17.7–18.6) was nearly 3.5 times that of suicide rate. This rate was higher in urban Bihar (10.2, 9.8–10.7) and was the highest in 45–54 years age group (28.0, 26.8–29.2). The deceased was beaten to death in 20.6% cases, shot by a gun in 14.3% cases, and killed by poisoning in 12.7% cases. Reason for homicide was not known in 47.6% cases, was personal dispute and money related in 19% each, and property dispute in 8% of the cases. Intentional injuries, especially homicide, cause a significant mortality burden in Bihar. These data have system-wide implications for prevention of suicides and homicides.